Work-life Balance: A Study On Banking Employees - Kaur , Rajwinder (Gyan Management Journal, 2020)
In today’s competitive business scenario, concept of balancing work and life becomes extremely essential because it affects workplace job satisfaction & employees commitment towards the company. The present study is undertaken in Banking Sector to identify the extent of balance in life and work and also to examine the impact of balanced work and life on employee. A survey was conducted after taking the approval from top management. For the present study, 250 questionnaires are filled by the different employees of different banks. The results of the study suggested that 41.20% of the employees feel imbalance in their work-life aspect. The main reasons of imbalance in work-life are work load with high job responsibility and stressful working hours with insufficient breaks in banking sector. The study also provides recommendations to improve balance in work-life.